Interplanetary magnetic field control of plasma distribution in the polar ionosphere. Issue 1 (1st January 2021) - Yang, Shenggao; Weng, Libin; Zhu, Yaguang; Yang, Xu; Hu, Sihui; Xu, Peikang; Zhang, Huan; Pan, Weidong; Shang, Jie; Su, Xing
Abstract: We used the TEC (Total electron content) data of 5 min resolution obtained from the Madrigal database during solar-maximum winter (Nov. 6, 2000–Feb. 4, 2001) to study statistically the polar ionospheric plasma distribution response to different intensity and orientation of IMF By/Bz components. The sunlit high-density plasma extension from dayside to nightside is favored in negative IMF By and Bz conditions. With the magnitude of the negative Bz increasing, the time range corresponding to the distinct high-density extension feature expands, and the plasma density along the extension path enhances, which can be attributed to the interaction between dayside solar-produced ionization whose poleward limit is decided by terminator and convection extent mainly modulated by IMF Bz component. As for IMF By component influence on the sunlit plasma extension, the combination effect of convection and corotation electric fields is necessary to be considered.